THE IMPORTANCE OF HEALTH EDUCATION IN FIRST AID FOR LAY PEOPLE: AN EXPERIENCE REPORT - da Silva Fonseca Lima, Gabriely; Cecon Gouveia, Ariane; Melquieses Campagnholi de Toledo, Ricardo; Cristina Rodrigues, Camila (Health and Society, 2023)
INTRODUCTION: Cardiovascular diseases are the main causes of death in the world, with 17.9 million people affected per year. In Brazil, it is estimated that around 320,000 deaths occur annually due to cardiorespiratory arrest (CPA), half of which occur in hospitals and the other half outside hospitals, such as in homes, shopping malls, airports, stadiums, among others. RESULTS AND DISCUSSION: Teaching first aid is extremely important considering that half of the occurrences of CA occur in the extra-hospital environment, and at any time, a lay individual can be surprised by an emergency situation, and as the person closest to the victim , this citizen will have the duty to direct. FINAL CONSIDERATIONS: Health education regarding first aid is a fundamental strategy to guarantee timely care and, consequently, increase the victims’ chances of survival, especially in schools, universities, companies and other community spaces, as that half of cardiorespiratory arrests occur in the out-of-hospital environment.